2002
DOI: 10.1194/jlr.r200004-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic origins and clinical significance of LDL heterogeneity

Abstract: LDLs in humans comprise multiple distinct subspecies that differ in their metabolic behavior and pathologic roles. Metabolic turnover studies suggest that this heterogeneity results from multiple pathways, including catabolism of different VLDL and IDL precursors, metabolic remodeling, and direct production. A common lipoprotein profile designated atherogenic lipoprotein phenotype is characterized by a predominance of small dense LDL particles. Multiple features of this phenotype, including increased levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
646
4
28

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(704 citation statements)
references
References 200 publications
26
646
4
28
Order By: Relevance
“…Furthermore, we identified gel filtration chromatography as a novel method for the isolation of TNFR1 exosome-like vesicles from plasma based upon the similar size of TNFR1 exosome-like vesicles and LDL particles. Consistent with this conclusion, immunoelectron microscopy revealed that TNFR1 exosomelike vesicles have a diameter of approximately 27-to 36-nm along their short axis, which is similar to, but slightly larger than LDL particles, which typically range from 18-to 23-nm size, although larger LDL particles of 27-to 28.5-nm have been described [12,18,19]. Despite the finding that TNFR1 exosome-like vesicles co-fractionated with LDL particles on the basis of size, they represented distinct particles based upon independent segregation characteristics on continuous sucrose gradients.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, we identified gel filtration chromatography as a novel method for the isolation of TNFR1 exosome-like vesicles from plasma based upon the similar size of TNFR1 exosome-like vesicles and LDL particles. Consistent with this conclusion, immunoelectron microscopy revealed that TNFR1 exosomelike vesicles have a diameter of approximately 27-to 36-nm along their short axis, which is similar to, but slightly larger than LDL particles, which typically range from 18-to 23-nm size, although larger LDL particles of 27-to 28.5-nm have been described [12,18,19]. Despite the finding that TNFR1 exosome-like vesicles co-fractionated with LDL particles on the basis of size, they represented distinct particles based upon independent segregation characteristics on continuous sucrose gradients.…”
Section: Discussionsupporting
confidence: 59%
“…We reasoned that if TNFR1 exosome-like vesicles represent a unique species of circulating microvesicles that are distinct from LDL particles, then it should be possible to differentiate the two populations on the basis of density, as LDL particles typically have a density ranging from 1.02 to 1.06 g/ml, whereas TNFR1 exosome-like vesicles from human vascular endothelial cells have a peak density of 1.11 g/ml [2,12]. As shown in Figure 3, LDL fractions from healthy volunteers were subjected to rate zonal centrifugation through continuous sucrose gradients and the density of LDL particles was determined using ApoB-100 as a marker.…”
Section: Tnfr1 Exosome-like Vesicles and Ldl Particles Represent Distmentioning
confidence: 99%
“…The mechanisms of the linkage between fat accumulation and sdLDL were investigated in previous studies. In obese children, relative weight correlated positively with hepatic lipase (Okada et al, 2004), which is considered to be a key enzyme for the production of sdLDL (Berneis and Krauss, 2002). Growth hormone also affects LDL particle size.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain this association: their low affinity to the LDL receptor, low resistance to oxidative stress, prolonged plasma half-life, high binding affinity to surface components in the vessel wall and efficient penetration into the intima (Chait et al, 1993;Chapman et al, 1998;Brewer, 1999). The formation of sdLDL is considered to involve several metabolic pathways that are influenced by genetic and environmental factors (Austin, 1994;Berneis and Krauss, 2002). Body fat accumulation is one of the important factors modifying the expression of sdLDL.…”
Section: Introductionmentioning
confidence: 99%
“…The atherogenicity of small dense LDL is related to its susceptibility to oxidative modification. (3,6,7) Oxidative modification can change the charge property of particles (8), and negatively charged LDL exerts various proatherogenic effects and properties, including cytotoxity, increased leukocyte recruitment, and impaired angiogenesis and LDL receptor binding. (9) Negatively charged LDL, which is generated through a peroxidative process, contains more lipoperoxides and cholesterol oxides and less -tocopherol than native LDL.…”
Section: Introductionmentioning
confidence: 99%